PENGOROK DAUN DAN POTENSI PARASITOIDNYA PADA BERBAGAI JENIS TANAMAN SAYURAN DI LEMBAH PALU, SULAWESI TENGAH - . Shahabuddin; Flora Pasaru; . Hasriyanty (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2014)
Leafminers and potency of their parasitoids at vegetable crops in Palu Valley, Central Sulawesi. Leafminer is an exotic pest and becomes a new important pest species of onion and other vegetable crops in Central Sulawesi. The study aimed to survey the leafminer species and its infestation level at several vegetable crops as well as the potency of their parasitoids as biocontrol agents. Therefore, several crops (onions, tomato, cabbage, string bean, lemon basil, amaranth) were observed to identify the leafminer species and their associated parasitoids. Several leaves of all crops infested by leafminers were collected for rearing the leafminers and their parasitoids in laboratory. The study recorded three species of leafminers:Liriomyza chinensis, L. sativae, and L. huidobrensis and five species of parasitoids: Hemiptarsenus varicornis, Chrysocharis pentheus, Sympiesis sp., Gronotoma micromorpha, and Opius sp. While Liriomyza chinensis was only recorded from onion crops (monophagus), other species were poliphagus. An average infestation level among leafminer species varied, i.e. 21% -51% while parasitism ranged were 13%-40 %. The most abundant parasitoid recorded from all observed crops was H. varicornis.The results suggest that parasitoids, mainly H. varicornis have a high potential to control leafminers in the vegetable crops in Palu Valley.